Portugal : Selected Issues. (IMF Staff Country Reports; Country Report, 1998)
This Selected Issues paper on Portugal reviews a set of issues of relevance to the regime change implied by European Monetary Union participation. It presents an empirical investigation of the business cycle in Portugal. The paper attempts to obtain a quantitative sense of the impact of monetary policy on the Portuguese economy, utilizing an unrestricted vector autoregression methodology to characterize the monetary transmission mechanism. It also examines some key forces at work in Portugal's external sector from different vantage points.